The effect of nanosilica on the intumescent fire-retardant coating’s properties: Rapid communication - Pyrzyński, Kajetan (Polimery, 2023)
The effect of nanosilica on the intumescent fire-retardant coating’s properties. Cone calorimetry and a single burning item test were used to determine flammability. The nanosilica-modified intumescent coating allows obtaining a Bs1d0 class non-flammable material for the protection of wood and wood-based materials (e.g., plywood, chipboard, fiberboard, other lignocellulosic composites).